Brand Activism as Value-Based Communication Strategy in Islamic Marketing: A Literature Review of Critical Consumers - Khairullah, Khairullah; Mulyadi, Mulyadi; Al fajar, Adam Hafidz (Universitas Islam Negeri Raden Intan Lampung, 2026)
The phenomenon of brand activism, as a value-based communication strategy, has emergedas a significant trend in modern marketing, including among Islamic brands. In the context ofthe increasing influence of critical Muslim consumers, particularly from the millennial andGeneration Z cohorts, brands are progressively expected not only to sell halal products butalso to advocate for relevant moral, social, and spiritual principles. This study systematicallyinvestigates, through a comprehensive review of existing literature, the utilization of brandactivism by Islamic brands as a strategic communication tool to meet the evolvingexpectations of critical consumers in the digital age. Employing a qualitative methodologyrooted in literature review, the research utilizes thematic content analysis of relevant, credible,and recent academic sources. The findings suggest that successful Islamic brands arecharacterized by their authentic and consistent expression of Islamic values in theircommunication efforts, notably through social campaigns, storytelling centered on corevalues, and proactive engagement on social media platforms. Such strategies foster emotionalloyalty and enhance consumer trust. Conversely, symbolic or manipulative forms of brandactivism tend to incite public opposition and skepticism. Thus, brand activism transcends meremarketing trend; it constitutes a strategic imperative in Islamic marketing communication—anapproach rooted in values that integrate spirituality, ethics, and the demands of a dynamicdigital marketplace.